Case Report: Coexistence of bullous pemphigoid and psoriasis: Therapeutic challenge and IL17A-targeted parallel treatment strategy - Drenovska, Kossara; Valeva, Elia; Shahid, Martin; Vassileva, Snejina (Frontiers in Medicine, 2023)
Autoimmune blistering diseases of the skin have all been reported in patients with psoriasis, bullous pemphigoid (BP) being the most frequently observed. The pathophysiologic triggers for BP in psoriatic patients are unclear. Recent observational studies have suggested that chronic psoriatic inflammation may cause pathological changes to the basement membrane zone, thus inducing autoimmunity against BP antigens through cross reactivity and “epitope spreading”. The coexistence of BP and psoriasis poses challenging therapeutic dilemmas related to the incompatibility of their standard treatments. Considering the probable common immunologic mechanisms in the pathogenesis of these inflammatory skin disorders, a suitable treatment regimen should be applied for their parallel control. We report three patients, who developed BP in the course of preceding long-lasting psoriasis. Secukinumab was administered as first-line treatment with marked therapeutic effect for both skin disorders and long-term disease control in two of the cases. In the third case, parallel disease control was initially achieved with methotrexate. A few years later, secukinumab was used for the treatment of a relapse of both dermatoses but worsening of BP was observed and methotrexate was reintroduced. Our experience on the therapeutic potential of secukinumab in BP is supported by the data in the literature. Recently, it was demonstrated that the proinflammatory cytokine IL17A has a functional role in the process of skin inflammation in BP, similarly to psoriasis. IL17A inhibition has emerged as a promising therapeutic strategy in patients with extensive or refractory BP but paradoxical development of BP after secukinumab treatment for psoriasis has also been described. This controversy emphasizes the need for further elaboration of optimal treatment strategies and recommendations.